The return of Sherlock Holmes - Doyle, Arthur Conan, Sir, 1859-1930.; Wordsworth Classics (London : Wordsworth Classics, 2000)
A collection of short stories in which Sherlock Holmes defies death and goes on to solve mysteries with his faithful sidekick Dr. Watson.
The empty house -- The Norwood builder -- The dancing men -- The solitary cyclist -- The priory school -- Black Peter -- Charles Augustus Milverton -- The six Napoleons -- The three students -- The golden pince-nez -- The missing three-quarter -- The Abbey Grange -- The second stain.
Adult
Keywords: Holmes, Sherlock (Fictional character) -- Fiction; Private investigators -- England -- Fiction; Mystery fiction; Private investigators -- Fiction; Short stories, English; England -- Fiction